THE STUDENTS’ PROBLEM-SOLVING SKILLS IMPROVEMENT BY USING INTEGRATION OF MEANS-ENDS ANALYSIS ON PROBLEM-BASED LEARNING MODEL - YUSRILIA PERMATASARI, NIKMATUS; NISWATI RODLIYATUL JAUHARIYAH, MUKHAYYAROTIN (Inovasi Pendidikan Fisika, 2020)
This research aims to describe the problem-solving skills of students after learning with problem-based learning (PBL) model integrated by a means-ends analysis (MEA) strategy on global warming material content. This type of research is quantitative descriptive, which categorized into the true-experimental design, with a non-equivalent control group design. The subjects in the investigations are students of class XI MNS in the even semester of the 2019/2020 school year of State Senior High School 2 Sidoarjo which includes two experimental classes (XI MNS 1 and XI MNS 2) and one control class (XI MNS 7), whereas the learning model used is PBL model with MEA strategy applied to the